ANALISIS KOEFISIEN ALIRAN PERMUKAAN PADA BERBAGAI BENTUK PENGGUNAAN LAHAN DENGAN SWAT - Danesta Ayu Saputri; Ridwan Ridwan; Mohamad Amin; Sandi Asmara (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2018)
Way Sekampung Hulu watershed definited as upstream part from Way Sekampung watershed with rain catchment area of 43,063 km2, that located in Tanggamus District of Lampung Province. Land shifting from non-building area to building area will stimulate the magnitude of surface water flow that impacts on the decline of recharge capacity and increased surface water flow that occurs flood in downstream area. The research aim to surface runoff coeffisient values in various land use form of watershed and hydrograph river flow parameter values. The method of this research is approach of hydrology model analysis based GIS, with SWAT model. Data of river flow debit, rainfall, and climatology that used is data record in 2010 until 2015. Process of model calibration with data record in 2010-2012 and model validation with data record in 2013-2015. Result of calibration process with SWAT-CUP are Nse and R2 value for river flow debit (flow out) of 0.63 and 0.66 respectively. Result of model validation are Nse and R2 value of 0.64 and 0.74 respectively. Surface flow coeffisient value (C) for shrubs of 0.13, settlement of 0.22, primary dryland forest of 0.11, open land of 0.44, moor of 0.28 and plantation of 0.15. Analysis result also obtained best values for hydrograph flow parameters such as SURLAG of 0.389, GW_REVAP of 8.451, SOL_AWC of 1.104, EPCO of 0.008, HRU_SLP of 0.898, SLSBBSN of 23.195, CH_N2 of 3.876, ALPHA_BF of 0.636, GW_DELAY of 8.451, ESCO of 1.335 and CN2 of 1.979.